Inside BAR (The Biblical archaeology review, 1984)
Bare granite mountains and mile after mile of sand interrupted here and there by an acacia tree—until 1967, this was the image conjured by the word "Sinai." But in that year, following the Six Day War, Israeli archaeologists started exploring Sinai. For the next 15 years—until Sinai was returned to Egypt as part of […]